Un archipiélago de resistencias - García-Teresa, Alberto (Verba hispanica, 2013)
Matias Escalera Corderos poetry is characterised by long verses; it is typically involved, deeply reflective and thought-provoking; it is aware of its own temporality, desires and intentions and presents a complex web of philosophical interconnections and tensions. It stands in contrast to the straight forward, superficial perception of life which contemporary society imparts to us. The poetry articulates an explicit dialogocity and duality, a dialectic indeed. This is poetry which presents an interesting juxtaposition of voices borne by constant, syntactic syncopations, like inserts which reannounce what has already been written and improvise on it, elaborating on it, correcting it, putting it more precisely, developing or even contradicting it, engaging in a conversation with it, forever expanding it. Thus, there are two levels of enunciation in the text, which converge in a somewhat incongruous perspective on the text and context, but which nevertheless leads to a very clear philosophical and political standpoint, one which pleads for heterogeneity and permanent contrastas a prequisite for understanding reality. In short, it provides us with the tools to take a fresh look at reality, which goes beyond appearances and whichseeks to reveal the deeper connections that tie events and people beyond the apparent remoteness of the present as shaped by our elusive modernity.
Keywords: Escalera Cordero, Matías, 1956-; španska poezija; literarne študije